REPRESENTASI OTHERNESS DAN DISKRIMINASI GENDER SERIAL BLUE EYE SAMURAI: ANALISIS SEMIOTIKA JOHN FISKE - Dwi Risqi Maulana; Teguh Hartono Patriantoro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the representation of otherness and gender discrimination in the series Blue Eye Samurai using John Fiske’s semiotic analysis. Employing a qualitative descriptive approach, the research examines three levels of meaning: reality, representation, and ideology. The findings reveal that Mizu faces racial discrimination due to her mixed heritage, symbolizing Japan’s obsession with racial purity, while Akemi experiences gender oppression under patriarchal control as a political instrument. Through visual symbols, dialogue, and narrative structure, the series critiques social systems that marginalize difference and female autonomy.